Implementation of the Importance Performance Analysis (IPA) Method in the Lecturer Performance Evaluation System at IBBI University Medan Based on the Balanced Scorecard - Jaman Amadi; S Sipur; F Fajrillah; Rizaldy Khair (CV. Media Digital Publikasi Indonesia, 2025)
In the era of globalization and increasingly competitive higher education, lecturer performance evaluation has become a crucial aspect for improving the quality of education. IBBI University Medan recognizes the importance of implementing an effective and efficient lecturer performance evaluation system to ensure that lecturers can make maximum contributions to the achievement of educational goals. The urgency of this research lies in the need to integrate the Importance Performance Analysis (IPA) method with the Balanced Scorecard (BSC) framework to create a comprehensive lecturer performance evaluation system. The main objective of this research is to implement and evaluate the effectiveness of the Importance Performance Analysis (IPA) method in the lecturer performance evaluation system at IBBI University Medan. This research uses a quantitative approach with a survey method to collect data from various stakeholders, including students, lecturers, and administrative staff. The collected data is then analyzed using the Importance Performance Analysis (IPA) method to identify gaps between expectations and realities in lecturer performance. The Balanced Scorecard is used as a framework to integrate the IPA results with the university's strategic objectives. This research is expected to provide valuable insights into the effectiveness of implementing the IPA method based on the Balanced Scorecard in the lecturer performance evaluation system. Through this research, IBBI University Medan aims to develop a lecturer performance evaluation system that is not only fair and transparent but also aligned with the university’s strategic goals, thereby contributing to the overall improvement of education quality.